ASSOCIATION OF THE METABOLIC SYNDROME CONSTITUENTS WITH MARKERS OF SUBCLINICAL TARGET ORGAN DAMAGE DURING FOLLOW-UP OF INTELLECTUAL LABORERS - O. P. Rotar; M. A. Boyarinova; E. V. Moguchaya; E. P. Kolesova; A. M. Erina; V. N. Solntsev; A. O. Konradi (Российский кардиологический журнал)
Aim. To evaluate the relation of metabolic syndrome (MS) and its constituents with markers of subclinical damage of target organs (TOD) in follow-up of almost healthy intellectual laborers.Material and methods. From the selection of 1600 employees of a bank we randomly selected 383 with at least one component of MS without cardiovascular disorders, of those by the end of 2 years period 331 came to final visit (response 86%). Mean age 46,6±9,0 y., mostly women (214 (64,6%)). All patients underwent anthropometry, blood pressure measurement (BP), lipids investigation, creatinine and fasting glucose, echocardiography with the assessment of the left ventricle hypertrophy (LVH), ultrasound study of carotid arteries (intima-media complex thickness — CIM, and atherosclerotic plaques), vascular rigidity assessment, anklebrachial index, albumin concentration in single portion of urine at both stages of observation.Results. While performing multiple logistic regression, presence of arterial hypertension (AH) associated with increased probability of LVH, thickening of CIM and higher vessel rigidity in standardization by gender and age. Relation of MS with the markers of TOD has not been found. In 2 years of follow-up there was a significant increase of patients with thickening of CIM (from 81 (24,5%) to 146 (44,1%), p<0,001) and decrease of LVH prevalence (from 154 (46,7%) to 109 (32,9%), p=0,003) together with significant decrease of BP and total cholesterol.Conclusion. Presence of AH is associated with higher probability of LVH and increased vessel rigidity, as atherosclerotic changes in carotid arteries. MS was not related with an increased prevalence of TOD, and the main predetermining factors for structural heart abnormalities, the vessels and kidneys, were gender and age. In 2 years of observation there was markedly decreased number of patients with LVH and kidney dysfunction at the background of BP pattern improvement, and increase of the number of patients with thicker CIM, regardless of a decrease of the hypercholesterolemia patients. In MS patients there was more common to use antihypertension treatments, that led to more prominent LVH regression.